Pengaruh Penerapan Model Pembelajaran Quantum Teaching Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMPN 1 IV Koto Tahun Ajaran 2019/2020 - MUTIA SRI RATNA DEWI (Departemen Matematika, 2019)
Mathematics communication plays very importance role in the mathematics learning which must be belonged and developed by the students. However, based on the result of observation in the class VIII at SMPN 1 IV Koto could be seen that mathematics communications ability still low. One of the solution is to apply the quantum teaching model. The purpose of this research is to describe is mathematic communication ability which used quantum teaching model is better than mathematics communication ability of students which learned with direct learning model and described the development of students’ mathematics communication ability which learned with quantum teaching model of learning in the class VIII at SMPN 1 IV Koto in the academic year 2019/2020. The kind of research is quasy exsperiment with Randomized Control Only Group Design planning model and hipotesis proved by t-test.from data anlyse could be concluded that students’ mathematics communication ability which learned with quantum teaching model of learning is better than students’ communication ability who learned with direct learning model at class VIII in SMPN 1 IV Koto at academic year 2019/2020.Keywords – quantum learning model, mathematical communication skill.Konsep Matematis